The Use of TikTok as a Learning Resource for Dialogue Text in Junior High School - Ratna Dwi Savitri; Joko Sukoyo (STAI Hubbulwathan Duri, 2023)
The impact of social media platforms on pedagogical practises has been significant, leading to the emergence of novel theoretical frameworks that prioritise connected learning in order to enhance educational outcomes. The proliferation of social media platforms has significantly contributed to the popularity of short movies, which were first designed based on micro-learning concepts. The social media platform TikTok has the potential to serve as an instructional tool in the future. The purpose of this study is to describe how and why students use the TikTok application to learn dialogue text in Javanese language classes. A detailed descriptive study is what this one is. This study was done at a private middle school in Semarang, Indonesia. Observation, structured interviews, and documentation are employed to collect data for this qualitative descriptive study's design. Using the Miles and Huberman model, data analysis was conducted through the steps of data collection, data reduction, data presentation, and drawing conclusions. The findings of this study are as follows: (1) the Tiktok application makes students more familiar with the material being taught; (2) the Tiktok application receives a positive response from students; and (3) the TikTok application is an effective learning medium, effective strategies for learning Javanese.